ANALYSIS OF MOS-1 MSR DATA RECEIVED AT SYOWA STATION, ANTARCTICA - ヤマノウチ, タカシ; オシヤマ, トモユキ; ワダ, マコト; YAMANOUCHI, Takashi; OSHIYAMA, Tomoyuki; WADA, Makoto (National Institute of Polar Research, 1992)
P(論文) Atmospheric parameters and ground surface information are obtained using the MOS-1 MSR data received at Syowa Station, Antarctica. Several difficulties have appeared in the process of deriving water vapor amount and liquid water content. One is the antenna temperature, which includes large bias error; this causes the largest uncertainty. Also, the antenna temperature near the coast of the Antarctic continent was greatly affected by high brightness temperature of the ice sheet owing to the antenna side lobe, which caused difficulties in comparing with ground-based observations as a validation. In the normal condition, for the present example, water vapor amount ranged from 0.4 to 1.4g/(cm)^2 and liquid water contentfrom 0 to 14mg/(cm)^2. However, there was found a belt of high liquid water content in some paths, corresponding to a high brightness temperature of about 190K. The atmospheric water vapor or liquid water affects the estimation of surface conditions such as sea ice concentration. It is difficult to obtain atmospheric parameters over the ice sheet and sea ice, on account of their high and variable brightness temperature. departmental bulletin paper